PEMANFAATAN SITUS WEB SEBAGAI SARANA PROMOSI DESASONGBANYU,KECAMATAN GIRI SUBO, GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - Muntoha Muntoha (Asian Journal of Innovation and Entrepreneurship, 2015)
Web page is the building blocks of websites, are documents, typically composed inplain text interspersed with formatting instructions of Hypertext Markup Language(HTML, XHTML). Those plain text are then connected to a web server that can beaccessed over a network such as the Internet, or a local area network (LAN) via theInternet addresses known as URL. By being in a web server, a website will be freelyaccessible to everyone. Freedom of access makes the website become the bestpromotional media today. Wide coverage into people is another reason to select awebsite as a media campaign. Desa Songbanyu which has many potential, especiallybeaches, should be able to take advantage of the website as media promotion. With theweb site of the village and community and village officials who are able to manage, DesaSongbanyu’s potential will be well-publicized and attract tourists